Application of silicon carbide in abrasive water jet machining - Khan, Ahsan Ali; Ali, Mohammad Yeakub (InTech, 2011)
Silicon carbide (SiC) is a compound consisting of silicon and carbon. It is also known as carborundum. SiC is used as an abrasive material after it was mass produced in 1893. The credit of mass production of SiC goes to Edward Goodrich Acheson. Now SiC is used not only as an abrasive, but it is also extensively used in making cutting tools, structural material, automotive parts, electrical systems, nuclear fuel parts, jewelries, etc. AWJM is a well-established non-traditional machining technique used for cutting difficult-to machine materials. Nowadays, this process is being widely used for machining of hard materials like ceramics, ceramic composites, fiber-reinforced composites and titanium alloys where conventional machining fails to machine economically. The fact is that in AWJM no heat is developed and it has important implications where heat-affected zones are to be avoided. AWJM can cut everything what traditional machining can cut, as well as what traditional machining cannot cut such as too hard material (e.g. carbides), too soft material (e.g. rubber) and brittle material (e.g. glass, ceramics, etc.). The basic cutting tool used in water jet machining is highly pressurized water that is passed through a very small orifice, producing a very powerful tool that can cut almost any material. Depending on the materials, thickness of cut can range up to 25 mm and higher (Kalpakjian & Schmid, 2010). A water jet system consists of three components which are the water preparation system, pressure generation system and the cutting head and motion system.